Nutrition and Feeding of Organic Poultry - Blair, Robert (CABI, 2014)
This publication sets out guidance for producers on nutrition and feeding practices that relate to the standards for certification of organic poultry. Details on permitted feed ingredients, with an emphasis on those grown or available locally and on suitable dietary formulations, are included. Although aspects of these topics have been presented at conferences and in trade and scientific publications, no comprehensive text has been published to date. Organic farming can be defined as an approach to agriculture in which the aim is to create integrated, humane, environmentally and economically sustainable agricultural production systems. Thus, maximum reliance is placed on locally or farm-derived renewable resources. In many European countries, organic agriculture is known as ecological agriculture, reflecting this emphasis on ecosystem management. The term for organic production and products differs within the European Union (EU). In English the term is organic; but in Danish, Swedish and Spanish it is ecological; in German it is ecological or biological; and in French, Italian, Dutch and Portuguese it is biological (EEC Regulation No 2092/91). In Australia the term used is organic, biodynamic or ecological